Numerical analysis of an oscillating water column converter considering a physical constraint in the chimney outlet - Gomes, Mateus das Neves (2015)
Submitted by Eliezer Mendes Lopes (mendesfurg@gmail.com) on 2015-05-27T18:18:44Z No. of bitstreams: 1 Numerical analysis of an oscillating water column converter considering a physical constraint in the chimney outlet.pdf: 487852 bytes, checksum: 428e9c4c32d1496be0322326e4514e71 (MD5)